Kajian dampak transformasi desain Nokia 3310 terhadap minat pasar Nokia di Indonesia - Kevin Ahmed Akbar (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2017)
Nokia mobile phone is one of the famous mobile phone brands carrying the slogan 'Connecting People' with the intention of presenting a mobile phone that can be used by everyone. Nokia is targeting a large market share, where every mobile phone made can be obtained by many people and with a design that is not inferior to other brands. One of the famous mobile phones ever produced by Nokia is the Nokia 3310 series which in its time Nokia 3310 phone is very in demanded because of its good design and resiliency. Then in 2017 comes the new Nokia 3310 series featuring a more modern design with a more developed specification than the previous Nokia 3310 series with the intention to hook the Nokia consumers who miss the Nokia 3310 but still feel the phone is not outdated. This research is a qualitative research based on the application of product design principles at Nokia 3310 - 2017.Keywords: tranformation, design, celuller phone, interest, market, spesification